Caveolin-1 is required for TGF-β-induced transactivation of the EGF receptor pathway in hepatocytes through the activation of the metalloprotease TACE/ADAM17 - Moreno-Càceres, J (Nature Publishing Group, 2014)
Transforming growth factor-beta (TGF-β) plays a dual role in hepatocytes, inducing both pro- and anti-apoptotic responses, whose balance decides cell fate. Survival signals are mediated by the epidermal growth factor receptor (EGFR) pathway, which is activated by TGF-β in these cells. Caveolin-1 (Cav1) is a structural protein of caveolae linked to TGF-β receptors trafficking and signaling. Previous results have indicated that in hepatocytes, Cav1 is required for TGF-β-induced anti-apoptotic signals, but the molecular mechanism is not fully understood yet. In this work, we show that immortalized Cav1(−/−) hepatocytes were more sensitive to the pro-apoptotic effects induced by TGF-β, showing a higher activation of caspase-3, higher decrease in cell viability and prolonged increase through time of intracellular reactive oxygen species (ROS). These results were coincident with attenuation of TGF-β-induced survival signals in Cav1(−/−) hepatocytes, such as AKT and ERK1/2 phosphorylation and NFκ-B activation. Transactivation of the EGFR pathway by TGF-β was impaired in Cav1(−/−) hepatocytes, which correlated with lack of activation of TACE/ADAM17, the metalloprotease responsible for the shedding of EGFR ligands. Reconstitution of Cav1 in Cav1(−/−) hepatocytes rescued wild-type phenotype features, both in terms of EGFR transactivation and TACE/ADAM17 activation. TACE/ADAM17 was localized in detergent-resistant membrane (DRM) fractions in Cav1(+/+) cells, which was not the case in Cav1(−/−) cells. Disorganization of lipid rafts after treatment with cholesterol-binding agents caused loss of TACE/ADAM17 activation after TGF-β treatment. In conclusion, in hepatocytes, Cav1 is required for TGF-β-mediated activation of the metalloprotease TACE/ADAM17 that is responsible for shedding of EGFR ligands and activation of the EGFR pathway, which counteracts the TGF-β pro-apoptotic effects. Therefore, Cav1 contributes to the pro-tumorigenic effects of TGF-β in liver cancer cells.